Improving the therapist’s metacognition and capacity to intersubjectively attune with a patient with psychosis through the exploration of the therapist’s developmental history: a case report - Salvatore, Gianpaolo; Di Somma, Tania; Buonocore, Luisa; Conza, Maria; Di Sturco, Nadia; Fimiani, Gerardina; Manfredi, Nicoletta; Marciano, Raffaella; Pallotta, Antonella; Proto, Maria Grazia; Sateriale, Anna (Frontiers in Psychiatry, 2023)
Clinical literature emphasizes how symptoms of psychosis can be efficiently targeted by psychological treatments. The most well-known approach to these symptoms is cognitive-behavioral therapy; but in the last few decades also other approaches are enriching the landscape, focusing on the dysfunctions in mentalization or metacognition, a spectrum of mental activities involving thinking about one’s own and others’ mental states. This huge amount of theoretical reflection and empirical research focused on the implementation of treatments does not seem to be associated with an attention to the inner world of the therapist who relates to the patient with psychosis; for example, to the impact of the therapist’s developmental history on the therapeutic relationship. In this paper the authors are inspired by an intersubjective perspective, according to which although the treatment is for the patient’s benefit, both the patient’s and the therapist’s developmental history and psychological organization are equally relevant for understanding the clinical exchange. On this basis, the authors make a “parallel” analysis of the clinical case of a young woman with symptoms of psychosis (i.e., persecutory delusions, auditory verbal hallucinations, social withdrawal) and its supervision process. They show how the therapeutic relationship can be significantly conditioned by the therapist’s developmental history; and how a process of supervision focused on the exploration of the traumatic elements of this history can effectively promote the therapist’s metacognitive capabilities, a functional patient-therapist intersubjective attunement, and a good clinical outcome.